2020
DOI: 10.3390/molecules25061408
|View full text |Cite
|
Sign up to set email alerts
|

Swellable Copolymers of N-isopropylacrylamide and Alkyl Acrylic Acids for Optical pH Sensing

Abstract: Swellable polymers that respond to pH (including a portion of the physiological pH range) have been prepared from N-isopropylacrylamide (NIPA) copolymerized with acrylic acid, methacrylic acid, ethacrylic acid or propacrylic acid by dispersion polymerization. When the swellable polymer particles are dispersed in a polyvinyl alcohol (PVA) hydrogel membrane, large changes occur in the turbidity of the membrane (which is measured using an absorbance spectrometer) as the pH of the buffer solution in contact with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…PNIPA copolymer with methacrylic acid showed reversible swelling both in 23 and 37 °C. [ 46 ] Zhang and Chu reported the effects of different polymerization temperature on the swelling/ deswelling kinetics and dynamic response of PNIPA gels prepared at 22, 0.5, and −20 °C in DMSO as the polymerization solvent. It was found that, in the shrinkage profiles of gels studied at 48 °C, the shrinkage rates of gels prepared at 0.5 and −20 °C are faster than those prepared at 22 °C.…”
Section: Resultsmentioning
confidence: 99%
“…PNIPA copolymer with methacrylic acid showed reversible swelling both in 23 and 37 °C. [ 46 ] Zhang and Chu reported the effects of different polymerization temperature on the swelling/ deswelling kinetics and dynamic response of PNIPA gels prepared at 22, 0.5, and −20 °C in DMSO as the polymerization solvent. It was found that, in the shrinkage profiles of gels studied at 48 °C, the shrinkage rates of gels prepared at 0.5 and −20 °C are faster than those prepared at 22 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Although a large number of studies have appeared in the literature on pH initiated swelling of acrylamide microgels [ 22 ], most of these studies have been limited to a specific pH-sensitive functional comonomer or a narrow temperature range. Only a few studies have been undertaken to delineate the effects of temperature and ionic strength on the pH response of a series of NIPA copolymers containing different pH-sensitive functional co-monomers [ 23 , 24 ]. However, the formulations used to synthesize these NIPA copolymers contained the same amount of pH-sensitive comonomer, NTBA, and crosslinker.…”
Section: Introductionmentioning
confidence: 99%